2003
DOI: 10.1620/tjem.201.139
|View full text |Cite
|
Sign up to set email alerts
|

Firearm-Related Mortality: A Review of Four Hundred-Forty Four Deaths in Diyarbakir, Turkey between 1996 and 2001

Abstract: The current study is based on a retrospective investigation of firearm deaths in Diyarbakir, which were autopsied by the Diyarbakir Branch of the Council of Forensic Medicine during the 6- year period. Four hundred-forty four deaths were investigated from January 1996 through December 2001, including homicide (296 cases, 66.7%), suicide (120 cases, 27%) and accidental shootings (28 cases, 6.3%). The age range of all firearm deaths in the study period was 5 to 75 years with a median age of 29.8 years. The major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
24
1
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 19 publications
9
24
1
7
Order By: Relevance
“…In several studies in our country this rate has been reported as between 11.70-32.7% [6,8,[33][34][35] and in studies in other countries as 6.5-73.9%. [5,27,32] Researchers have reported a strong relationship between access to firearms and suicide.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In several studies in our country this rate has been reported as between 11.70-32.7% [6,8,[33][34][35] and in studies in other countries as 6.5-73.9%. [5,27,32] Researchers have reported a strong relationship between access to firearms and suicide.…”
Section: Discussionmentioning
confidence: 57%
“…This rate has been reported as ranging between 0.13-24% in previous studies. [4][5][6]8,11,[33][34][35] Copeland and Ornehult made a detailed study of accidental firearms deaths together with crime scene investigation and it was reported that the firearms accidents could have occured as a result of playing with firearms, showing the weapon others or because of faulty firearms. [39,40] These features are similar to the findings of accidental deaths in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is attributed to the local characteristics of the province of south and southeast cities of our country. Falling off roofs and balconies stems from the fact that family members, including children, tend to sleep on roofs and balconies without banisters and barriers in order to alleviate the intense heat and humidity in this part of the Turkey in summer months (Gören et al 2003a). Burns and scalds are also significant in childhood home injuries.…”
Section: Discussionmentioning
confidence: 99%
“…ise %40.5 oran›nda bafl-boyun, %14.9 oran›nda kar›n, %12.6 oran›nda gö¤üs bölgesinin yaraland›¤›n› bildirmifltir (27). Çal›flma-m›zda da Gören ve ark.…”
Section: Resim 3 Evde Bulunan Av Tüfe¤i Ile Kardefli Ile Oynarken Kunclassified